Breast Cancer - Mayrovitz, Harvey N. (Exon Publications, 2022)
Breast cancer has become the most diagnosed cancer globally, surpassing lung and prostate cancers. In 2020, 2.3 million females were diagnosed with breast cancer worldwide. The incidence and related mortality from breast cancer continue to grow despite remarkable advances in our understanding of the biology of breast cancer and the availability of better therapeutic options. Therapies currently used to treat metastatic breast cancer extend the survival and quality of life of patients, but they are not curative. Therefore, a better understanding of the mechanisms involved in metastatic dissemination is of pivotal importance. This book provides a unique blend of carefully presented and structured information covering a broad array of relevant breast cancer-related issues. The first eight chapters cover breast cancer epidemiology, etiology, subtypes, current and emerging surgical innovations to treat and image breast cancer, a description of noninvasive lymphedema assessment methods to detect and track this important treatment complication, and the potential role of platelets and galectins in breast cancer metastasis. The last five chapters are devoted to the description of forward-looking albeit potential breast cancer treatment possibilities. In this regard, different chapters of the book describe novel research on the potential of ubiquitin-specific protease 18 (USP-18), ribosomal protein S6 kinase 1 (RPS6K1), the lysosomal system, nanoparticles, and proteolysis target chimeras as therapeutic agents for breast cancer. The range of clinical and translational research of breast cancer presented in this book will be of interest to healthcare professionals, clinicians, and basic scientists.